2021
DOI: 10.1002/ejlt.202100085
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Temperature and Oxygen Dose During Rendering of Goose Fat to Promote Fatty Acid Profiles

Abstract: The effect of two fat rendering systems of goose fat, sous‐vide and conventional oven baking, on fatty acid and volatile compound profiles, color, and lipids oxidation, is evaluated during refrigerated storage. Low temperature rendering increases polyunsaturated fatty acids and decreases saturated fatty acids concentration (P ≤ 0.05). The obtained results show that oxygen deprivation reduces the fat oxidation process. A discriminant model is designed using principal component analysis. Aldehydes are the domina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 38 publications
1
0
0
Order By: Relevance
“…A similar trend was also observed for the grilled burgers, where the variant S-100% had the best nutritional parameters. Similar Al values (0.24) were found in the study by Rodríguez-Carpena et al [48], who used avocado oil, sunflower oil, and olive oil as fat substitutes. Depending on the fat substitute and the type of vegetable fat source used, they affect the health index scores to different degrees [32,42,49].…”
Section: The Analysis Of Fatty Acid Compounds and Health Indicatorssupporting
confidence: 87%
“…A similar trend was also observed for the grilled burgers, where the variant S-100% had the best nutritional parameters. Similar Al values (0.24) were found in the study by Rodríguez-Carpena et al [48], who used avocado oil, sunflower oil, and olive oil as fat substitutes. Depending on the fat substitute and the type of vegetable fat source used, they affect the health index scores to different degrees [32,42,49].…”
Section: The Analysis Of Fatty Acid Compounds and Health Indicatorssupporting
confidence: 87%
“…The level of denaturation for myosin, collagen, and actin was ascertained based on the curves, according to the methodology outlined by Agafonkina et al (2019) [42]. The denaturation level for each protein was calculated by comparing the enthalpy of denaturation between the untreated and heat-treated samples using Equation (7). The DSC analyses were conducted thrice for each sample.…”
Section: The Protein Denaturation Levelmentioning
confidence: 99%
“…Meeting these consumer expectations requires not only excellent breeding and nutrition but also a precise understanding of the processes influencing the final product's quality [4]. The quality of goose meat thus becomes a key competitive factor in the food market, affecting not only health but also overall consumer satisfaction [5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…Organoleptic analyses revealed that, after a month of storage, no deterioration was seen in samples with green tea extract. The benefits of adding plant extracts such as rosemary extract, oregano, black tea, sage, and thyme to lard in order to inhibit lipid oxidation have been the subject of various reports [20][21][22]. Their activity was effective in the inhibition of fats oxidation at a concentration of 0.01%, and also exhibited antimicrobial efficiency.…”
Section: Introductionmentioning
confidence: 99%